2021
DOI: 10.33394/jo-elt.v8i2.4345
|View full text |Cite
|
Sign up to set email alerts
|

Four C’s Skills Integration in the Lesson Plans of Grade 7 English Teacher

Abstract: Four C skills’ integration in English curriculum has been investigated in recent years. Unfortunately, those studies focused on the integration of 4Cs in lesson plans carried out in elementary schools. Thus, this research aimed to analyze how the 4C skills were implemented in English lesson plans of 7th grade. The data were collected through content analysis on ten lesson plans of public and private junior high schools in Jakarta and Bekasi. It was found that all analyzed lesson plans have incorporated the 4Cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The ten analyzed lesson plans in this present study incorporate Communication, Collaboration, Critical Thinking, and Creativity, covering on average more than 50% of indicators of each skill, proving that the teachers are aware of the importance of the 4Cs in the learning process so they put the indicators into the lesson plans. Similar results were also found by Tamela & Dwi (2021) when researching the integration of the 4C skills in the English lesson plans of grade 7, revealing that all the analyzed lesson plans incorporated Communication, Collaboration, Critical Thinking, and Creativity skills. Some indicators were incorporated in all lesson plans regardless of the topics, while others only appeared in lesson plans with certain topics.…”
Section: B Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The ten analyzed lesson plans in this present study incorporate Communication, Collaboration, Critical Thinking, and Creativity, covering on average more than 50% of indicators of each skill, proving that the teachers are aware of the importance of the 4Cs in the learning process so they put the indicators into the lesson plans. Similar results were also found by Tamela & Dwi (2021) when researching the integration of the 4C skills in the English lesson plans of grade 7, revealing that all the analyzed lesson plans incorporated Communication, Collaboration, Critical Thinking, and Creativity skills. Some indicators were incorporated in all lesson plans regardless of the topics, while others only appeared in lesson plans with certain topics.…”
Section: B Discussionsupporting
confidence: 79%
“…The results suggested that senior secondary English teachers in Indonesia could design lesson plans that incorporate 4C skills despite different development plans in terms of the 4C skills indicators they include, depending on the topic on which they are based. In parallel with that, Tamela & Dwi (2021) conducted research about an analysis of 4C skills integration in the lesson plans of English for grade 7. Some indicators were incorporated in all lesson plans regardless of the topics they had.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of educators, learners are given opportunities to discover their innovativeness in preparation to their global competitiveness in the 21st century. Ojo (2019) and Tamela and Dwi (2021) found that the 4Cs are interconnected because of the following interweaving indicators as the students undertook. Communication is needed in the collaborative tasks, and collaborative learning needs critical thinking and performance of the projects entails the use of creativity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tuzlukova et al, 2018;Erdogan, 2019;Imamyartha et al, 2019 The integration of 4Cs for 21st century learning should not be isolated. They need to be emphasized in all instructions Tamela and Dwi, 2021 Instructors should seriously consider what objectives they are going to achieve at the end of lessons. Ojo, 2019;Sunardi and Doringin, 2020;Azhary and Ratmanida, 2021 A classroom should be equipped with modern tools for learning and paired with suitable 21st century designed tasks.…”
Section: General Pedagogical Findingsmentioning
confidence: 99%